ACUM, an easily underdiagnosed cause of dysmenorrhea—A case report - Hu, Qicai; Guo, Chunlei; Chen, Qing; Zhang, Wei; Wang, Huifang; Wei, Weixia (Frontiers in Medicine, 2024)
This report described 3 cases with long-term severe dysmenorrhea and were referred to our department for medical help. The diagnosis of Accessory cavitated uterine malformation (ACUM) was considered based on symptoms and ultrasound/MRI features. After that, combined hysteroscopic surgery and laparoscopic surgery was performed, no complications occurred during surgery or in post-operative period. Always keep ACUM in mind in patients with severe dysmenorrhea not responding to medical management. Surgery is the most effective treatment for this anomaly.